Building a Departmental Culture Using Data, Behavior, and Humility - Diane Myers (Academic Chairpersons Conference Proceedings, 2020)
This presentation focuses on how behavioral strategies, data-based decision making, and a healthy dose of humility (and humor) can create a departmental culture that promotes faculty, staff, and student success. Discussions and activities will center on creating and communicating expectations, determining priorities, and creating a collaborative community.
Keywords: behavioral strategies; data-based decision making; culture; leadership